Risk-value efficient portfolios and asset pricing - Günter Franke; Martin Weber (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
Portfolio choice is usually modelled by von Neumann-Morgenstern utility. Risk-value models are more general and permit the derivation of risk-value efficient frontiers. A behaviorally based risk measure with an endogenous or exogenous benchmark is used to derive efficient portfolios and to analyse the implied equilibrium asset pricing. In risk-value models a richer set of sharing rules is obtained than in a von Neumann-Morgenstern world. Linear sharing rules are obtained only for quadratic risk functions. If the risk function is modelled by a negative HARA-function, then sharing rules are convex or concave relative to each other. Hence, agents buy and sell portfolio insurance motivating trade in options. Asset pricing, however, is similar to that in a von Neumann-Morgenstern world.
Keywords: 330; Portfolio-Management; Risiko; Entscheidungstheorie; CAPM; Theorie